2020
DOI: 10.1001/jamanetworkopen.2020.2142
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Medicare Expenditures and Adverse Events for Patients With Acute Myocardial Infarction, Heart Failure, or Pneumonia in the United States

Abstract: IMPORTANCE Studies have shown that adverse events are associated with increasing inpatient care expenditures, but contemporary data on the association between expenditures and adverse events beyond inpatient care are limited. OBJECTIVE To evaluate whether hospital-specific adverse event rates are associated with hospitalspecific risk-standardized 30-day episode-of-care Medicare expenditures for fee-for-service patients discharged with acute myocardial infarction (AMI), heart failure (HF), or pneumonia. DESIGN,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…For example, it is known that hospitalized patients who experience safety-related adverse events are at greater risk of readmission. 7 , 8 , 9 , 10 What is not known is whether the CMS readmission measure conveys information about a hospital’s safety. Specifically, do patients admitted to hospitals with a higher risk-standardized 30-day all-cause readmission rate have a higher risk of a safety event while hospitalized?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it is known that hospitalized patients who experience safety-related adverse events are at greater risk of readmission. 7 , 8 , 9 , 10 What is not known is whether the CMS readmission measure conveys information about a hospital’s safety. Specifically, do patients admitted to hospitals with a higher risk-standardized 30-day all-cause readmission rate have a higher risk of a safety event while hospitalized?…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is known that hospitalized patients who experience safety-related adverse events are at greater risk of readmission. [7][8][9][10] What is not known is whether the CMS readmission measure conveys information about a hospital's safety.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 805,000 AMIs that occur in the United States per year, it is estimated that a quarter are recurrent, with recurrent AMIs associated with a twofold increase in 5-year mortality versus index AMIs [ 1 , 7 ]. Costs associated with CV-related hospitalizations have been found to be $20,000 higher than non-CV related hospitalizations (all costs reported in this article are in US dollars) [ 8 ], and Medicare expenditures for AMI in the 30-day period have been found to be higher than for other CV-related conditions such as heart failure [ 9 ]. Moreover, there is growing evidence that readmission burden for AMI extends beyond the typical 30-day period [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Costs associated with CV-related hospitalizations have been found to be $20,000 higher than non-CV related hospitalizations (all costs reported in this article are in US dollars) [ 8 ], and Medicare expenditures for AMI in the 30-day period have been found to be higher than for other CV-related conditions such as heart failure [ 9 ]. Moreover, there is growing evidence that readmission burden for AMI extends beyond the typical 30-day period [ 9 , 10 ]. A recent study found that approximately a quarter of AMI episodes in the USA are associated with readmission within 90 days, an increase of approximately 65% on the proportion readmitted within 30 days [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature estimating incremental 30-day Medicare expenditures associated with any of the 21 adverse events captured by the MPSMS yielded estimates similar to ours. 21 However, the MPSMS does not contain data on all of the same HACs as the PSI 90 score and contains data on adverse events other than HACs, making direct cost and spending comparisons difficult. 18 Our finding that most HACs were associated with significant reductions in hospital outpatient care spending is also consistent with the literature.…”
Section: Discussionmentioning
confidence: 99%